Determination of Influential Countries by Cultural and Geographical Parameters - Tuğal, İhsan; Karcı, Ali (Muş Alparslan Üniversitesi, 2020)
Thecultural and geographical situation of countries cover the most importantfactors determining the relations between countries. In this study, a newmethod was proposed to identify the influential countries. Similarities werecalculated by religion, language, zone, and landmass information of countries.This data was transformed into a graph structure.  Central countries were determined by Shannonand Karcı entropy over country similarities. The number of similarities andsimilarity ratios of each country with other countries were used when identifyingthe influential countries. The difference of Karcı entropy from Shannon, thatthe effect of these two values ??can be adjusted by the alpha. With theparameters used, the determination of countries'leadership will reveal newanalysis and perspectives in international relations.

Ülkelerinkültürel ve coğrafi durumu, ülkeler arasındaki ilişkileri belirleyen en önemlifaktörlerdir. Bu çalışmada çizge entropi kullanılarak, sosyal ağ analiziyöntemleri ile lider ülkeler tespit edildi. Ülke benzerlikleri kültürel vecoğrafi parametreler olan din, dil, bölge, kıta bilgileri ile ölçüldü. Benzerliklerkullanılarak ülkelerin ilişki yapısı çizge yapısında çıkarıldı. Sosyal ağyapısında merkezi ülkelerin tespiti için geleneksel merkezilik ölçümleri yerineShannon ve Karcı entropi kullanıldı ve elde edilen sonuçlara göre bu ikientropi türü kıyaslandı. Karcı entropi de Shannon’dan farklı olarak bu ikideğerin ölçümdeki etkisinin alfa ile ayarlanabildiği gösterildi. Bu çalışmadakullanılan parametrelerle elde edilen sonuçlar ve önerilen yöntemler ileülkelerin liderliğinin ve etkinliğinin belirlenmesi uluslararası ilişkilerdeyeni analizler ve bakış açıları ortaya çıkaracaktır.
Kültürel ve Coğrafi Parametrelere Göre Lider Ülkelerin Tespiti
anemon
Keywords: country associations; social computing; graph entropy; influential countries; social network; sosyal hesaplama; çizge entropi; lider ülkeler; ülke birliktelikleri; Sosyal Ağ